Biodegradable Mg-based alloys: biological implications and restorative opportunities. (19th May 2023) - Lin, Xiao; Saijilafu,; Wu, Xiexing; Wu, Kang; Chen, Jianquan; Tan, Lili; Witte, Frank; Yang, Huilin; Mantovani, Diego; Zhou, Huan; Liang, Chunyong; Yang, Qiang; et al.
ABSTRACT: Mg-based alloys as revolutionary implantable biomaterials have increasingly attracted considerable attention, owing to their biodegradability in vivo and beneficial effects on biological systems. The degradation process and products of Mg-based alloys have been reported to exhibit significant biological effects on host-tissue responses. However, these effects have not yet been fully understood. This review systemically summarizes and analyses the current understandings and recent research progress in this area. The primary focal points are the biological effects and related mechanisms associated with the degradation behaviour of Mg-based alloys. The biological impacts of the degradation products are elucidated and the arguable or controversial issues are also discussed, providing a pathway toward a greater understanding of the biological implications of Mg-based alloys. Furthermore, based on these biological implications, the restorative potential of Mg-based alloys for applications in tissue repair and regeneration is summarized. Finally, outlooks on biosafety evaluation and design strategies for Mg-based alloy implants are briefly discussed.